A Review on Virtual Reality Skill Training Applications - Xie, Biao; Liu, Huimin; Alghofaili, Rawan; Zhang, Yongqi; Jiang, Yeling; Lobo, Flavio Destri; Li, Changyang; Li, Wanwan; Huang, Haikun; Akdere, Mesut; Mousas, Christos; Yu, Lap-Fai (Frontiers in Virtual Reality, 2021)
This study aimed to discuss the research efforts in developing virtual reality (VR) technology for different training applications. To begin with, we describe how VR training experiences are typically created and delivered using the current software and hardware. We then discuss the challenges and solutions of applying VR training to different application domains, such as first responder training, medical training, military training, workforce training, and education. Furthermore, we discuss the common assessment tests and evaluation methods used to validate VR training effectiveness. We conclude the article by discussing possible future directions to leverage VR technology advances for developing novel training experiences.